A New Wind Turbine Concept: Design and Implementation - Kekezoglu, Bedri; Tanrioven, Mugdesem; Erduman, Ali (BUDAPEST TECH, 2015)
Electrical energy demand has been continuously increasing. Depleting fossil fuel reserves, environmental concerns, and insufficiency of conventional generation techniques in meeting growing demand, renewable energy use has been widely adopted in the world. When considering the application of renewable energy sources in the world, it can be seen that wind energy is mostly preferred over other renewable energy sources. In this study, a new prototype wind energy conversion system suitable for urban use is designed and manufactured. The proposed design is modular and has flexible structure. In the new design, an outer gear ring attached to turbine blades is used. In the design stage, both the number of blades and the number of outer gear rings are varied to analyze their effect on turbine performance. Performance analysis of the prototype wind turbine is completed under real life conditions and results are given. As a result of this study, it is shown that increasing the gearwheels and blade numbers caused turbine output power increases. The most efficient structure identified during the field analysis is a three gearwheel with six blade system.
Keywords: renewable energy resources; wind energy; wind turbine prototype; urban use; PERFORMANCE; Engineering